2011
DOI: 10.4132/koreanjpathol.2011.45.6.659
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Melanoma Arising in an Ovarian Mature Cystic Teratoma - A Case Report and Literature Review -

Abstract: Ovarian primary malignant melanoma is very uncommon with only 44 reported cases in the literature. A 71-year-old woman with an ovarian mass and multiple nodules in the liver presented to our hospital. She was treated with bilateral salpingo-oophorectomy, and malignant melanoma was found in the mature cystic teratoma of the ovary. Malignant melanoma cells were also found in the ascitic fluid. She died 5 months later. Here we report a very uncommon case of malignant melanoma arising in an ovarian mature cystic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…4 Although the current authors agree that one cannot rule out a rare possibility of a regressed cutaneous primary melanoma presenting with ovarian metastasis, the positive peritoneal biopsy and fluid cytology in the presence of ovarian melanoma strongly points to ovarian origin. 4,16 It has also been suggested that, if an ovarian cystic teratoma is associated with markedly elevated levels of CA-19-9, lactate dehydrogenase (LDH), and squamous-cell carcinomarelated antigen, there is a strong possibility of a malignant melanoma arising in a teratoma. 17 In the current case the patient had elevated levels of LDH and other markers were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…4 Although the current authors agree that one cannot rule out a rare possibility of a regressed cutaneous primary melanoma presenting with ovarian metastasis, the positive peritoneal biopsy and fluid cytology in the presence of ovarian melanoma strongly points to ovarian origin. 4,16 It has also been suggested that, if an ovarian cystic teratoma is associated with markedly elevated levels of CA-19-9, lactate dehydrogenase (LDH), and squamous-cell carcinomarelated antigen, there is a strong possibility of a malignant melanoma arising in a teratoma. 17 In the current case the patient had elevated levels of LDH and other markers were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Less frequent histologic types include adenocarcinoma, sarcomas, thyroid carcinoma, malignant melanoma, and neuroectodermal tumors, among others (Table 1). 10,13–56 Carcinomas can arise from any mature epithelial tissue. Squamous cell carcinoma in mature cystic teratoma arises from the epidermal component via a carcinoma in situ pathway, or from the respiratory epithelium via squamous metaplasia/dysplasia/carcinoma in situ pathway 2,7,11 .…”
Section: Histopathologymentioning
confidence: 99%
“…Symptoms are usually non-specific, arising from the presence of a tumor in the pelvis minor and general malignancy and include general weakness, loss of appetite, weight loss, abdominal distension, early satiety, lower abdominal pain, lower back pain, abdominal fullness, although the course may also be asymptomatic [31,41,42]. The first symptoms may be organ-specific and related to the metastatic focus.…”
Section: Characteristicsmentioning
confidence: 99%
“…In the case of a patient with brain metastases, the first symptoms were headache, dizziness, nausea, vomiting and photophobia [38]. In 10 of the 18 analyzed cases, patients had metastases involving the pelvic organs, bowel, appendix, omentum, brain, lung, liver and adrenal gland already at the beginning of the diagnostic process [33,35,36,[38][39][40][41][42].…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation